2020
DOI: 10.1128/jb.00747-19
|View full text |Cite
|
Sign up to set email alerts
|

Rap Protein Paralogs of Bacillus thuringiensis: a Multifunctional and Redundant Regulatory Repertoire for the Control of Collective Functions

Abstract: Quorum sensing (QS) is a mechanism of synthesis and detection of signaling molecules to regulate gene expression and coordinate behaviors in bacterial populations. In Bacillus subtilis, multiple paralog Rap-Phr QS systems (receptor-signaling peptides) are highly redundant and multifunctional, interconnecting the regulation of differentiation processes such as sporulation and competence. However, their functions in the Bacillus cereus group are largely unknown. We evaluated the functions of Rap proteins in Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
12
0
2
Order By: Relevance
“…In contrast, B. thuringiensis is a soil-inhabiting, insect-pathogenic, and saprophytic bacterium (87) that may use its Rap repertoire to regulate virulence, sporulation, Cry toxin production, nutrient scavenging, and dispersal. Accordingly, we recently found that the lab strain B. thuringiensis Bt8741 has expanded the regulation of extracellular proteases to six out of the eight Rap proteins encoded in its genome (80). This contrasts acutely with only one Rap protein involved in the regulation of extracellular proteases in B. subtilis (83).…”
Section: Evolution and Ecology Of Multifunctionality And Redundancy Omentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, B. thuringiensis is a soil-inhabiting, insect-pathogenic, and saprophytic bacterium (87) that may use its Rap repertoire to regulate virulence, sporulation, Cry toxin production, nutrient scavenging, and dispersal. Accordingly, we recently found that the lab strain B. thuringiensis Bt8741 has expanded the regulation of extracellular proteases to six out of the eight Rap proteins encoded in its genome (80). This contrasts acutely with only one Rap protein involved in the regulation of extracellular proteases in B. subtilis (83).…”
Section: Evolution and Ecology Of Multifunctionality And Redundancy Omentioning
confidence: 97%
“…First, although several Rap protein paralogs are encoded in both B. subtilis and the B. cereus group genomes, they have diversified independently after speciation, with no known examples of horizontal transfer between the two groups; therefore, no Rap homolog is shared between these groups. That is, all Rap proteins from B. subtilis share a common ancestor, while all Rap proteins for the B. cereus group share a different common ancestor (23,78,80); second, NprR, which targets Spo0F in the B. cereus group, is not found in B. subtilis. Additionally, not all of the cell differentiation processes from B. subtilis are shared in the B. cereus group species; for example, homologs of the ComP-ComA two-component system are largely absent in species from the B. cereus group (79).…”
Section: Evolution and Ecology Of Multifunctionality And Redundancy Omentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, sólo existe un estudio sobre la interacción bacteria-insecto en Bt (Verplaetse et al 2015), en donde se logró observar que el principal gen que se expresan sobre el cadáver del insecto es el regulador de virulencia PlcR, además se presenta heterogeneidad en su expresión, es decir que se generan subpoblaciones durante esta interacción. Proponemos que nuestras cepas reporteras son un recurso valioso para estudios futuros sobre la regulación genética en diferentes aspectos del ciclo de vida de Bt, que es un tema de interés en nuestro grupo de investigación en CIAD-CIDEA (Rocha et al 2010: Rocha et al 2012Cabrera et al 2014;Cabrera et al 2016;Gastélum et al 2020;Verdugo et al 2020). Además, pueden ser útiles para seguir caracterizando la fisiología bacteriana en sistemas de fermentación de Bt para su uso biotecnológico, como también se ha hecho en el grupo de investigación en UAM-I (Lima et al 2019).…”
Section: Discussionunclassified
“…Además, NprR regula la transcripción de genes involucrados en la formación de bio-película (Slamti et al 2014) y regula el inicio de la esporulación (Cabrera et al 2014). Además de NprR, 6 proteínas Rap de Bt regulan la producción de proteasas extracelulares, y por lo tanto son importantes para la regulación del desarrollo del necrotrofismo (Gastélum et al 2020).…”
Section: Necrotrofismo En Btunclassified